EQUIVALENCE IN NEWS HEADLINESTRANSLATION: ENGLISH HEADLINES RENDERED INTO BAHASA INDONESIA IN BBC WEB NEWS - Diah Supatmiwati; Zainudin Abdussamad (Humanitatis : Journal of Language and Literature, 2020)
Equivalence is the leading subject in translation studies; hence, a wide range of hypotheses on equivalence have been discussed in detail within this field translation over the recent decades. Equivalence in translation is influenced by many different factors, i.e., parts of importance among words and articulations, language structure and participants in various communicative circumstances, semantics, pragmatics, etc. The concept of equivalence with the focus on equivalence degrees is provided; the overview and characterization of the main features, as well as specifics of translation of media language (headlines in particular), are presented in the article as well. The paper focuses on the equivalence in the translation of headlines of on-line news articles since headlines are considered as crucial and the most important part of news articles. The translation of news headlines across certain journalistic cultures, specifically focusing on headlines translated from English into Bahasa Indonesia. Headlines are an extraordinary type of text, which are considered a separate genre on their own. Since a headline is an entrance to the news details, journalists have to utilize different techniques to make the headline concise, effective, and eye-catching to the reader. 40 English headlines and their Indonesian translations have been selected for the analysis which is performed according to the degrees of equivalence: optimum translation, partial equivalence, zero equivalence. Partial equivalence is divided into two narrower subtypes which are: near-optimum and weak translation. The results show that over some translation procedures have been implemented in rendering headlines.